2017
DOI: 10.15761/jdd.1000103
|View full text |Cite
|
Sign up to set email alerts
|

The role of endocannabinoids in the control of eating disorders

Abstract: Eating Disorder (ED) is a syndrome characterized by persistent alteration of eating behavior and the conditions that cause an insufficient ingestion and/or adsorption of foods. There are three different ED diseases: Anorexia Nervosa (AN), Bulimia Nervosa (BN) and Binge Eating Disorders (BED). ED are complex conditions that arise from a combination of long-standing behavioral, emotional, psychological, interpersonal, and social factors. The neuronal circuits that control the ingestion of food are mainly related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Although several components of the ECS may be involved, CB1 receptors appear crucial for the central and peripheral effects of cannabinoids on eating behavior [26]. CB1 receptors are widely expressed in reward-related brain regions [14], initially suggesting a role in the motivation to eat [26]. A well-known example of THC's effect on eating behavior is marijuana-induced "munchies".…”
Section: The Endocannabinoid System Regulates Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Although several components of the ECS may be involved, CB1 receptors appear crucial for the central and peripheral effects of cannabinoids on eating behavior [26]. CB1 receptors are widely expressed in reward-related brain regions [14], initially suggesting a role in the motivation to eat [26]. A well-known example of THC's effect on eating behavior is marijuana-induced "munchies".…”
Section: The Endocannabinoid System Regulates Food Intakementioning
confidence: 99%
“…In addition to its involvement in appetite regulation and reward-based eating, several investigations indicate that the ECS is involved in many aspects of eating disorders and obesity [3,26,114]. Interestingly, studies in patients with psychiatric conditions have revealed relationships between ECS gene polymorphisms and their pathological state [114].…”
Section: Binge Eating Disorder and The Endocannabinoid Systemmentioning
confidence: 99%
“…If it is presynaptic and with adenylate Cyclase inhibition, it may be generated hyperpolarization with a consequent decrease in neurotransmitter release. If it is postsynaptic, the action of rCB1 is on K + channel regulation and adenylate cyclase inhibition [7,9]. The neuromodulatory action of AEA is due to the following characteristics: they have distinct synthetic pathways; their cell release occurs after membrane depolarization and calcium intake; and its action is terminated with its reuptake and degradation by an intracellular enzyme (fatty acid amide hydrolase) [10].…”
Section: Introductionmentioning
confidence: 99%